Navigating the Complexities of Sarcoidosis: A Case Study Analysis - Vadakkepatt, Anisha; Naze, Amita; Ajee, K L (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Sarcoidosis is a multisystem chronic inflammatory disorder that can affect practically all organs and is characterized by noncaseous epithelial cell granulomas and abnormalities in tissue architecture. In this case report, an Indian-origin female patient in her late 40’s was identified as having systemic sarcoidosis, which had affected her lungs and caused granulomas to form. The patient is initially had a long term persistent severe dry cough and shortness of breath. It took two years to confirm the condition through chest X-ray. And after the condition was confirmed, the requisite corticosteroid therapy was started, and a regular follow up showed a sustained improvement in pulmonary function. This case study emphasizes how crucial it is to distinguish the problem from another diagnosis to start the appropriate treatment immediately. Also, this case study highlights the efficacy of corticosteroid therapy particularly when there is no extrapulmonary involvement.